Prinsip-Prinsip Dasar Moderasi Beragama Dan Implementasinya Dalam Kepemimpinan Kepala Sekolah - Ruhana Nur Fadilah; Arfi Putri Maharani; Siska Melina Rahmawati; Tamrin Fathoni (Tamilis Synex: Multidimensional Collaboration, 2023)
principles of religious moderation can be implemented in the leadership of school principals in the educational environment, as well as their impact on an inclusive and harmonious school environment.The research methods used may include literature studies to understand the concept of religious moderation, interviews with school principals who implement the principles of religious moderation, and data analysis to evaluate the effectiveness of implementing religious moderation in school leadership.It is hoped that the research results will provide valuable insight into the importance of religious moderation in the educational context, as well as provide recommendations for school principals and other educational stakeholders to apply the principles of religious moderation in school leadership to create an inclusive and harmonious learning environment for all related parties.It is hoped that this research can make a positive contribution in promoting tolerance, cooperation between religious communities, and strengthening the values of moderation in education as a foundation for building a peaceful and harmonious religious society.